2017
DOI: 10.3906/bot-1608-10
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of flowers at two developmental stages in Thermopsis turcica (Fabaceae)

Abstract: IntroductionPlant development is controlled by the interplay of multiple environmental cues and endogenous signals.High-throughput approaches such as proteomics, transcriptomics, and metabolomics have provided immense amounts of data, leading to a better understanding of biological processes (Hochholdinger et al., 2006). As the relationship between mRNA expression levels and protein abundance is poor, proteomics provides functional gene expression profiles during biological processes (Komatsu and Hossain, 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous work has reported that the dominant bacteria at the rhizomes of V. turcica is Bacillus megaterium (Çiftçi, 2018) and the researcher assumed that B. megaterium has the potential growth-promoting effects on V. turcica. Yildiz et al (2017) studied the proteomic analysis in V. turcica and proteins involved in flower development were identified. There has been only one study existed on the genetic classification of V. turcica, and it has been based on the nucleotide sequence of the nuclear ribosomal internal transcribed spacer region (ITS) (Uysal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has reported that the dominant bacteria at the rhizomes of V. turcica is Bacillus megaterium (Çiftçi, 2018) and the researcher assumed that B. megaterium has the potential growth-promoting effects on V. turcica. Yildiz et al (2017) studied the proteomic analysis in V. turcica and proteins involved in flower development were identified. There has been only one study existed on the genetic classification of V. turcica, and it has been based on the nucleotide sequence of the nuclear ribosomal internal transcribed spacer region (ITS) (Uysal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%